Technology Acceptance Model and the Role of Trust to the Paths to Online Customer Loyalty in an Emerging Market - Nguyen, Thi Tuyet Mai (2016)
The technology acceptance model has been well-known for decades. However, the global adoption of the Internet creates new interests in utilizing TAM in e-commerce and the post-consumption intention, especially in emerging markets. Data was collected from 758 online customers via a web-based survey in Vietnam. Particular contribution of the results is that perceived usefulness, perceived ease of use, fairness, trust and the quality of the customer interface have direct or indirect impacts on customer satisfaction and customer loyalty.